2017
DOI: 10.1002/adem.201700294
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heating Elements for Induction Welding of Carbon Fiber/Polyphenylene Sulfide Thermoplastic Composites

Abstract: Conductive films of carbon nanofibers (CNFs) decorated/coated with metals, either silver (Ag) or nickel (Ni) are fabricated using a solution casting process and used as novel heating elements (HEs) for induction welding of carbon fiber/ polyphenylene sulfide (CF/PPS) thermoplastic composites. Prior to making the films, the metal-coated CNFs are prepared by an electroless plating method using Ag or Ni precursors. A solution of the metal-coated CNFs is then casted onto a pure PPS film to give a robust conductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In the literature, a wider range of studies on nanocomposite films as susceptors for the induction welding of TPCs or induction heating of adhesives have been carried out. Farahani et al showed that silver nanoparticle-based thermoplastic films are suitable as susceptors for induction welding, reaching melting temperature in less than 50 s at 400 A [ 40 , 41 ]. However, the potential for disassembly and the repair of fusion bonded TPC joints has not been investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a wider range of studies on nanocomposite films as susceptors for the induction welding of TPCs or induction heating of adhesives have been carried out. Farahani et al showed that silver nanoparticle-based thermoplastic films are suitable as susceptors for induction welding, reaching melting temperature in less than 50 s at 400 A [ 40 , 41 ]. However, the potential for disassembly and the repair of fusion bonded TPC joints has not been investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastics are superior in toughness and environmental resistance and are superior to most thermosetting resins in terms of their short processing time, incombustibility, and long lifecycle. Additionally, thermoplastics can be produced quickly at low cost [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Induction heating (IH) is used in industry, medicine, household, et cetera [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40]. As non-ionizing radiation it is applied to trigger or to control physical processes and chemical reactions (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The overall heating properties of particulate embedded susceptors are difficult to predict because these various factors, (a) to (d), are related to each other by complex behavior [2]. A poor adhesion with the surrounding polymer can create defects within the polymer and lead to residual stress at the interfaces and, probably, excessive deformation [32].…”
Section: Introductionmentioning
confidence: 99%